Universal Entanglement Revival of Topological Origin - Chen, Dongni; Chesi, Stefano; Choi, Mahn-Soo (2024)
We have analyzed the dynamics of entanglement in dissipative fermionic and bosonic Su-Schrieffer-Heeger (SSH) models and found that, when the decoherence channel preserves the chiral symmetry, they exhibit a revival of entanglement in a wide range of parameters. This behavior only emerges in the topological phase, with the visibility of the revival dropping to zero at the phase boundary. Furthermore, the revival acquires a universal character once the system size exceeds the localization length of the edge modes. Our findings indicate that the universal entanglement revival has its origin in the topological properties of the SSH model. These dynamical properties may be experimentally accessible, for example, using photonic quantum computers.